Visualization of fast calcium oscillations in the parafascicular nucleus - Hyde, James (2013)
The parafascicular nucleus (Pf) is an ascending target of the pedunculopontine nucleus (PPN) and is part of the “non-specific” intralaminar thalamus. The PPN, part of the reticular activating system, is mainly involved in waking and rapid eye movement sleep. Gamma oscillations are evident in all Pf neurons and mediated by high threshold voltage-dependent N- and P/Q-type calcium channels. We tested the hypothesis that high-speed calcium imaging would reveal calcium-mediated oscillations in synchrony with patch clamp recorded oscillations during depolarizing current ramps. Patch-clamped 9 to 19-day-old rat Pf neurons (n = 148, dye filled n = 61, control n = 87) were filled with Fura 2, Bis Fura, or Oregon Green BAPTA-1. Calcium transients were generated during depolarizing current ramps and visualized with a high-speed, wide-field fluorescence imaging system. Cells manifested calcium transients with oscillations in both somatic and proximal dendrite fluorescence recordings. Fluorescent calcium transients were blocked with the nonspecific calcium channel blocker, cadmium, or the combination of ω-Agatoxin-IVA (AgA), a specific P/Q-type calcium channel blocker and ω-conotoxin-GVIA (CgTx), a specific N-type calcium channel blocker. We developed a viable methodology for studying high-speed oscillations without the use of multi-photon imaging systems.